2007
DOI: 10.1038/sj.onc.1210889
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 deficiency inhibits v-ras-induced transformation by suppression of JNK MAPK signaling and increased farnesyl transferase inhibition

Abstract: The ability of transforming growth factor-b (TGF-b) to modulate various effects on distinct cell lineages has been a central feature of its multi-faceted nature. The purpose of this study was to access the effects of deletion of a key TGF-b signal transducer, Smad3, on MAPK activation and v-Ras Ha -transformation of primary mouse embryonic fibroblasts (MEFs). We observe reduced TGF-b1 and v-ras Ha mediated activation of the JNK and ERK MAPK pathway upon ablation of Smad3. Further, Smad3-deficient MEFs demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
4
10
0
Order By: Relevance
“…A recent report has shown that the ablation of Smad3 can inhibit the activation of JNK and ERK induced by TGF-ß1 and v-ras, thereby protecting mouse embryonic fibroblasts from oncogenic transformation (17). We also observed reduced TGF-ß1-mediated phosphorylation of JNK and ERK1/2 when dominant negative Smad2 was transfected into rat MCs, leading to a decrease of collagen IV expression.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…A recent report has shown that the ablation of Smad3 can inhibit the activation of JNK and ERK induced by TGF-ß1 and v-ras, thereby protecting mouse embryonic fibroblasts from oncogenic transformation (17). We also observed reduced TGF-ß1-mediated phosphorylation of JNK and ERK1/2 when dominant negative Smad2 was transfected into rat MCs, leading to a decrease of collagen IV expression.…”
Section: Discussionsupporting
confidence: 54%
“…Moris et al showed that JNK-dependent phosphorylation of Smad2 and Smad3 in response to HGF, PDGF and TGF-ß, can transactivate target genes with no loss of R-Smad capacity (16). The suppression of JNK MAPK signaling by the deletion of Smad3 inhibits v-Ras-induced transformation in primary mouse embryonic fibroblasts (17). Furthermore, the p38 pathway is activated by TGF-ß1, and then stimulates Smaddependent transcription through SUMO-1-mediated modification of Smad4 in NIH3T3 and COS7 cells (18 (19).…”
Section: Introductionmentioning
confidence: 99%
“…For example, transforming growth factor-b activates both JNK and ERK pathways via Ras in mouse embryonic fibroblasts. 44 Secondly, because the bFGF effect on fibroblast proliferation becomes evident after quite a long period of stimulation in our study, the rapid activation of ERK1 ⁄2 and JNK1 pathways may indirectly influence the proliferation. Thirdly, the long incubation period of HDFs in the presence or absence of bFGF should increase confluency of cells, which may affect the activation state of ERK1 ⁄2 or JNK1.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the influence of linker phosphorylation on COOH-tail phosphorylation has been an unsettled subject with various data suggesting that mitogen-mediated linker phosphorylation either inhibits (Kretzschmar et al 1999; Engel et al 1999; Wicks et al 2000; Grimm and Gurdon 2002; Mori et al 2004; Ho et al 2005; Javelaud and Mauviel 2005; Sekimoto et al 2007; Arany et al 2008; Hamajima et al 2009; Millet et al 2009; Lin et al 2010; Hong et al 2010) or enhances (Brown et al 1997; de Caestecker et al 1998; Oft et al 2002; Funaba et al 2002; Hayashida et al 2003; Furukawa et al 2003; Matsuura et al 2004; Yoshida et al 2005; Kamaraju and Roberts 2005; Yang et al 2008; Wang et al 2009; Matsuzaki et al 2009; Alarcón et al 2009; He et al 2010; Matsuura et al 2010; Sasseville et al 2010; Rachakonda et al 2010; Jiang et al 2010; Burch et al 2010; van der Velden et al 2011) events downstream of TβRI. Possible explanations exist for these different outcomes.…”
Section: Spatial and Temporal Dynamics Of R-smad Phosphoisoforms: Difmentioning
confidence: 99%